The Oldest Vakufnama in Yugoslavia - Kaleši, Hasan (Prilozi za orijentalnu filologiju, 2017)
Until several years ago there existed in Bitolj (Manastir) a mosque called "Eski cami" (The Old Mosque). lt was the oldest mosque in our regions and one of the old est in the Balkans. Its founder was Sungur bey, called Čauš-bey, one of the commanders of sultan Murat Il. It seems that Cauš came from the region of Bitolj and that he was taken to Istanbul by means of devlirme. Coming back from a campaign against Skenderbey in Albania, he stopped in Bitolj and he settledthere. He built there the mentioned mosque and then a medresa and a zavija, remnants of which can still be seen in Bitolj. Cauš-bey also bull t a mesdžid in Jedren and another one in Vidin. For maintenance of these institutions he founded a foundation consisting of 25 shops, one han (inn), two pieces of land, 7 mills, 1 vineyard in Bitolj and another 11 shops and 17 rooms in Jedren and a mill in Vidin. Čauš-bey made his vakfija legal between 9th and 19th April1435. This vakufnama written in Arab represents, in fact, the oldest Arabic or Turkish document discovered so far in Yugoslavia. The original of this document has not been discovered, but its copy is to be found in the sidžil of the seriat court in Manastir, No. 99, which is kept in Državni arhiv (State Archives) in Skopje. The author of this paper gives a critical view of the text of vakufnama. Its translation is accompained by historical annotations and by explanations and fascimiles from the mentioned sidžil. If we compare this vakfija with other Macedonian ones we can see that it influenced the form of vakfijas in later period.